The effect of apparent amylose content and dietary fibre on the glycemic response of different varieties of cooked milled and brown rice. - Trinidad, T. P.; Mallillin, A. C.; Encabo, R. R.; Sagum, R. S.; Juliano, B. O. (2003)
Brown rice is a good source of dietary fibre (DF) and contains higher vitamins/minerals than milled rice. The study determined the effect of amylose content (AC) and DF on glucose response (GR) from different varieties of milled and brown rice. Milled and brown rice were used as test foods. They were fed to 9-10 human volunteers containing 50 g available carbohydrate after an overnight fast. GR and the glycemic index (Gl) were determined. Results found that Sinandomeng with the lowest AC had a high Gl = 75, while PSBRc10 with the highest AC had a low GI = 50. Sinandomeng with a low DF had GI = 75, while its brown rice had GI = 55. Brown rice (IR64) with 23% AC and DF of 2.5 g/100 g had low GI = 51. In conclusion, the GR and Gl of the different varieties of cooked milled and brown rice varied depending on its AC and DF contents.
Keywords: Brown rice; Rice; Rice, Enriched